2017
DOI: 10.1139/cjfr-2016-0497
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fuelwood properties and correlations of fuelwood properties with wood density and growth in five tree and shrub species in Niger

Abstract: Information about variation and correlations of fuelwood properties and growth is needed in order to recommend species and sites for fuelwood production in a changing climate in Africa. We investigated the effects of site variables (land use, soil, terrain), geographical coordinates, and mean annual rainfall on fuelwood properties (volatile matter, fixed carbon, ash content, moisture content, gross calorific value, gross calorific value per cubic metre, and fuel value index) of Combretum glutinosum Perr., Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…However, in hardwood plantations, including Eucalyptus spp., the effect of increased growth rate is still unclear (Saranpää 2003;Carrillo et al 2015;Ko et al 2017). In this study, slow growing trees on unburned sites had higher density than faster growing trees on burned sites, consistent with reports by King et al (2006), Sotelo Montes et al (2017, and Pretzsch et al (2018). However, other studies did not find a relationship between rate of growth and wood density in Eucalyptus (Quilhó and Pereira 2001;Saranpää 2003).…”
Section: Bark Thickness and Wood Densitysupporting
confidence: 84%
“…However, in hardwood plantations, including Eucalyptus spp., the effect of increased growth rate is still unclear (Saranpää 2003;Carrillo et al 2015;Ko et al 2017). In this study, slow growing trees on unburned sites had higher density than faster growing trees on burned sites, consistent with reports by King et al (2006), Sotelo Montes et al (2017, and Pretzsch et al (2018). However, other studies did not find a relationship between rate of growth and wood density in Eucalyptus (Quilhó and Pereira 2001;Saranpää 2003).…”
Section: Bark Thickness and Wood Densitysupporting
confidence: 84%
“…Indeed, the CAC/ RCP 68-2009 (2009) reported that the combustion of wood with lower moisture content is rapid and leads to high PAHs production. Sotelo et al (2017) and Sotelo et al (2012)…”
Section: Distribution Of the Pah Concentrations In Rumuzu And Kilichi Jamentioning
confidence: 99%